The Devastating Impact of Heavy Metal Contamination on Plant Growth and Development: Unveiling Phytotoxicity and Exploring Remediation Strategies - Ataitiya, Hylalibiya; Ahmad, Kabiru Bashir; Kaugama, Aminu Ado; Idris, Shamsu Abdullahi; Adam, Ansar Bilyaminu; Abubakar, Musa Yahaya; Mathew, Twan Sale (Darul Yasin Al Sys, 2024)
Heavy metal contamination poses a significant threat to plant growth and development, leading to reduced crop yields, impaired ecosystem functioning, and potential human health risks. This review provides a comprehensive overview of the phytotoxic effects of heavy metals on plant species, highlighting the mechanisms of uptake, transport, and accumulation. We explore the devastating impacts on plant morphology, physiology, and biochemistry, including altered root architecture, reduced photosynthesis, and impaired reproductive development. This review highlights the urgent need for effective remediation approaches to mitigate the phytotoxic effects of heavy metals and ensure sustainable ecosystem functioning. We identify knowledge gaps and future research directions, emphasizing the importance of interdisciplinary collaboration to address this critical environmental issue.